Các hợp chất phenolic được phân lập từ lá cây bạch hạc Rhinacanthus nasutus (L.) Lindau / Trần Minh Ngọc, Nguyễn Thị Thanh Phương, Triệu Duy Điệt - Trần, Minh Ngọc
Five phenolic compounds including trans o-coumaric acid propanoic acid 3,4-dimethoxyphenyl-1-O- β -D-apiofuranosyl(1-2)-β-D-glucopyranoside